The Effects of Sectoral Trade Composition on Inequality: Evidence from Emerging Economies - Islam, Mohammad Monirul; Li, Zhaohua; Fatema, Farha (Asian Journal of Empirical Research, 2017)
This study identifies the effect of sectoral composition of trade on inequality in the emerging economies. We separate export and import into four broad sectors such as agriculture; labor-intensive manufacturing; capital-intensive manufacturing and service, and measure revealed comparative advantage (RCA) of each sector. We then identify the effect of growing export; import; and comparative advantage of these sectors on inequality. The study applies dynamic panel data model to a panel dataset of 31 emerging economies over 1994-2014. We take both relative and absolute measures of inequality to solve the debate regarding measurement issues of inequality. The study results suggest that trade in different sectors have differential effect on inequality measured by Gini and ratio of average income of highest and lowest quintiles, but it significantly increases income differences between the two extreme quintiles of income group. Technology has a mixed effect on relative inequality, but it substantially raises absolute income differences between the highest and lowest quintiles.